Pengaruh Makroekonomi dan Spillover Effect Harga Batubara Terhadap Harga Saham Perusahaan Batubara - Mahendra, Rizky Cahya; Biyanto, Frasto; Miswanto, Miswanto; Siregar, Baldric (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to examine whether macroeconomic factors (inflation and SBIS) and coal prices affect the stock prices of coal production companies. The research adopts a quantitative approach using secondary data from the period 2017–2021, with a total of 244 observations. The data were analyzed using panel data analysis techniques. The population consists of 24 coal production company stocks, from which 4 samples were selected through purposive sampling. Statistical calculations were conducted using EViews software. The findings indicate that increases in stock prices of coal production companies are more effectively influenced by inflation and coal prices, both of which shape investors’ perceptions of the companies’ prospects. Inflation plays an important role as an external factor that can suppress stock prices through reduced purchasing power and increased economic uncertainty. In contrast, coal prices serve as a key indicator reflecting the companies’ performance and revenue potential. On the other hand, SBIS has not shown a significant effect on stock prices and therefore is not a primary factor in investment decision-making within this sector. Consequently, investors are advised to pay closer attention to inflation dynamics and coal price movements as a basis for investment considerations. Meanwhile, companies need to improve their operational performance and take advantage of favorable commodity price conditions to sustainably enhance firm value.